Differences In Physical Development And Basic Movement Activities Between Students In The Mountains And Students In The Coastal Plains In Primary School Physical Education Learning In Ngaras District - Fajar Sukmana; Trio Deswa Rahman; Yuda Gastriana Putra; Adang Sudrazat (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to analyze the differences in physical development and basic motor activity between students in mountainous areas and students in coastal plains in elementary school physical education (Penjas) learning in the Ngaras District. This research uses a quantitative method with a comparative design. The research sample consisted of 20 elementary school students, 10 students from elementary schools in mountainous areas and 10 students from elementary schools in coastal plains. The research instruments used were anthropometric tests (height, weight, chest circumference, and waist circumference), physical fitness tests (running test, push-up test, and sit-up test), and basic motor activity tests. The data were analyzed using a t-test. The results showed that there were significant differences in physical development and basic motor activity between students in mountainous areas and students in coastal plains. Students in mountainous areas had a higher average height, weight, and chest circumference than students in coastal plains. Students in mountainous areas also had higher physical fitness and basic motor activity test scores than students in coastal plains. This study concludes that there are significant differences in physical development and basic motor activity between students in mountainous areas and students in coastal plains in elementary School Physical Education (PE) learning in Ngaras District. Factors that are suspected to influence this difference are environmental factors, genetic factors, and socio-economic factors.